Recent advances in itaconic acid production from microbial cell factories - Gopaliya, Deeksha; Kumar, Vinod; Khare, Sunil Kumar (Elsevier, 2021)
Itaconic acid is an unsaturated organic acid with two carboxyls and one methylene group. The presence of these functional groups, along with a conjugated double bond, makes itaconic acid a versatile molecule with a vast number of applications. Itaconic acid can be produced through chemical as well as biological routes. Aspergillus terreus is the most prevalent microbial cell factory for the biological production of itaconic acid, reaching titers of >100 g/L. However, it suffers from low yield and volumetric productivities leading to high manufacturing costs. The wider applications of itaconic acid can be enabled with a low-cost production process, which can be achieved with cheaper feedstocks and robust cell factories accumulating itaconic acid efficiently. The current review summarizes the recent advances in the biological production of itaconic acid with a focus on the metabolic engineering of prokaryotic and eukaryotic systems for the overproduction of itaconic acid. It comprehensively describes various microbial cell factories with an insight into the pathway leading to itaconic acid production in natural producers like A. terreus and U. maydis. It also discusses the metabolic engineering approaches to improve strain performance in terms of high itaconic acid productivity, less by-product generation, and the ability to utilize unconventional cheap substrates. Moreover, the alternative strategies for the development of non-native producers through genome engineering and the hurdles related to itaconic acid production have been elaborated.
Keywords: Itaconic acid; Metabolic engineering; Bioprocess engineering; Polymer industry